Respuesta :
Answer:
C. None of the above. The correct expression is 2(y-4)
Step-by-step explanation:
Given the expression -2y-8+4y, we are to find the equivalent expressed is which other expression is similar to it. This can be expressed as shown below;
Step 1: Collect the like terms of the expression
= -2y-8+4y
= (-2y+4y)-8
Step 2: Sum up the terms in parenthesis:
= (-2y+4y)-8
= 2y-8
Step 3: factor out the common terms
= 2y-8
= 2(y-4)
Hence the equivalent expression is 2(y-4).
Answer:
A and B
Step-by-step explanation:
On Khan Academy its right.